Analisis Aplikasi “Layanan Syariah Linkaja” Perspektif Fatwa Dewan Syariah Nasional (DSN) MUI no. 116/DSN-MUI/ix/2017 Tentang Uang Elektronik Syariah dan Maslahah Mursalah - Fadilah Qotimatun Puji Rahayu; Muh. Nashirudin (Journal on Education, 2023)
This study aims to explain (1) an analysis of the practice of the LinkAja Sharia Service application viewed from the perspective of DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017 concerning Sharia electronic money, (2) analysis of electronic money (e-money) in the LinkAja Sharia Service application in terms of Maslahah Mursalah. The research will be conducted in 2022. This research is a field research. using a qualitative research approach with data collection techniques using interviews and documentation. Checking the validity of the data using triangulation. Data analysis data was carried out through three stages, namely data reduction, data presentation and drawing conclusions. The results of this study are (1). LinkAja's sharia service is the first digital wallet in Indonesia that uses sharia principles, which has received an official certificate from DPS MUI and permission from Bank Indonesia. LinkAja's sharia services are in accordance with the Fatwa of the MUI National Sharia Council No. 116/DSN-MUI/IX/2017 concerning Sharia Electronic Money both general provisions and specific provisions as well as the legal provisions used. (2) Electronic money (e money) in the LinkAja application in terms of maslahah mursalah there are several menus available in LinkAja sharia services. there are 3 (three) categories of levels of needs. For LinkAja sharia services, there are only 2 categories of needs, namely: hajjiyat (secondary needs) and maslahah tahsiniyah (tertiary needs) owned by LinkAja sharia services.